(untitled) (Scientia Agropecuaria, 2021)
The white ball (Guazuma crinita Mart, Meliaceae) as one of the most important species in the Ucayali region due to its rapid growth and increasing market value, makes it a competitive species when choosing species for a program of production of goods and sustainable services, therefore determining the amount of biomass plays a key role for this purpose; In this purpose, the 38 trees of G. crinita at 31 months of age, with an average diameter at the height of the base of 13.33 cm, with a maximum and minimum value of 17.4 and 10.2 cm, respectively, with a standard deviation of 1.80 cm and a variability coefficient of 13%, for an average total biomass of 28.76 Kg, with a standard deviation of 10.07 and a variability coefficient of 35%; It was determined that there is a high relationship between the independent variable diameter at the height of the base (dab) and the total aerial biomass of the trees in the Aguaytia river basin according to the biomass model a*dab^b, which resulted which is predictable with the following formula Bmadab = 0.04253*dab2.5027 with R2 = 0.9397.